ANALYSIS OF GRAMMATICAL ASPECTS OF THE TALK SHOW SENTILAN SENTILUN EDITION “DPR LIBRARY FOR WHOM?” - Juni Mahsusi; Baiq Yulia Kurnia Wahidah (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
Abstract This study aims to determine what grammatical aspects are used in the Sentilan Sentilun discourse "DPR Library for Whom?" and what grammatical aspects are most dominantly used in the discourse. The method used in this research is descriptive qualitative. This research needs to be done to find out the grammatical aspects of Sentilan Sentilun discourse. In addition, this research is also expected to add the enrichment of research on talk show discourse. This study uses discourse analysis techniques. The data source in this study is the Sentilan Sentilun talk show "DPR Library for Whom?". The data in this study are lingual units in the form of words, clauses, or sentences contained in the speech of the Sentilan Sentilun talk show " DPR Library for Whom?". The data in the study were analyzed using discourse analysis techniques, namely descriptive text analysis, interpretation, and explanation. The results of this study found several grammatical aspects contained in the Sentilan Sentilun text, including references, substitutions, ellipsis, and conjunctions. There are 3 forms of reference grammatical aspects: personal reference, demonstrative reference, and comparative reference. Persona references are 195, demonstrative references are 274, and comparative references are 2. The following grammatical aspect is substitution. The substitution in the Sentilan Sentilun talk show discourse is only in 2 clauses. In addition, the discourse of the Sentilan Sentilun talk show, grammatical aspects of the ellipsis were also found. The ellipsis contained in the discourse consists of 20 words, 31 phrases, 2 clauses, and 1 sentence. While the grammatical aspects of conjunctions are found in several forms, causality is 20 contradictions, 31 excesses 5, objectives 1, additives 20, as many as 13 alternatives, and sequential as many as 7. The dominant grammatical aspect that appears is the demonstrative reference, with a total 274. Keyword: discourse analysis, talkshow discourse, grammatical aspects.